1993
DOI: 10.2307/1939512
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Overlap, Competition, and Priority Effects in Larval Anurans

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. Interspecific competitors often colonize communities at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(143 citation statements)
references
References 32 publications
3
137
3
Order By: Relevance
“…It was experimentally shown that early and synchronized reproduction (i.e. after pond formation or filling) can be more advantageous for larval growth and development than late breeding, because of competition and predation pressure from the larvae of early breeders (Morin et al 1990;Lawler & Morin 1993;Petranka & Thomas 1995). Toads tend to exploit newly formed breeding habitats or those that have became useful for reproduction due to the increased hydroperiod.…”
Section: Resultsmentioning
confidence: 99%
“…It was experimentally shown that early and synchronized reproduction (i.e. after pond formation or filling) can be more advantageous for larval growth and development than late breeding, because of competition and predation pressure from the larvae of early breeders (Morin et al 1990;Lawler & Morin 1993;Petranka & Thomas 1995). Toads tend to exploit newly formed breeding habitats or those that have became useful for reproduction due to the increased hydroperiod.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors can affect the intensity of early ontogenetic interactions, including temperature, productivity, and the relative timing of adult breeding and offspring hatching. For example, relative timing of appearance among early life stages of amphibians in small ponds can dramatically affect community structure by determining the outcome of competitive interactions (Lawler and Morin 1993). These relative timing effects also are important for larval fishes, affecting interspecific competition and thus the relative growth, survival, and abundance of species within a community (Garvey and Stein 1998a).…”
Section: Variation In Early Interactionsmentioning
confidence: 99%
“…In amphibians that breed in temporally variable habitats, breeding and hatching asynchronies frequently result in priority effects that structure communities, with early breeders generally having a competitive or predatory advantage over late breeders (e.g., Lawler and Morin 1993;Margalit 1994, 1996;Boone et al 2002; but see Harris 1980). For many species that utilize seasonal wetlands as nuptial-natal sites, breeding in the population is synchronous and coincident with pond-filling, thus reducing or eliminating intraspecific priority effects.…”
Section: Introductionmentioning
confidence: 99%